¿Dónde termina mi casa?: Mirando el hábitat residencial desde la noción de experiencia - Iturra Muñoz, L (Universidad de Chile, Instituto de la Vivienda, 2014)
The ability to conceptualize the residential habitat is related to the different ways in which this can be questioned. This is why the physical-spatial approach, associated with the material and spatial constitution of housing or inhabitable spaces, has been the traditional method to explore this issue. Such a situation has resulted in residential habitat being related to the concept of dwelling as a delimited space associated with some form of ownership. This paper uses a self-ethnographic account to build a dialogue between the concept of residential habitat and the notion of experience, thus offering new possibilities for the conceptualization, questioning and visualization of habitat. Such an exercise introduces the idea of continuity and indivisibility about the experience of inhabiting a given place.